Capital consolidation as factor of competitiveness - Nikitina, Tatyana (My University, 2013)
The research of the role of capital’s consolidation for country’s economic development and competitiveness.
Keywords: consolidation of enterprises’ capital; country’s international competitiveness; консолідація капіталу; міжнародна конкурентоспроможність країни; кафедра готельно-ресторанної справи